2012
DOI: 10.1021/jz300318v
|View full text |Cite
|
Sign up to set email alerts
|

Delocalized Lattice Plasmon Resonances Show Dispersive Quality Factors

Abstract: This Letter describes how out-of-plane lattice plasmon (OLP) resonances in 2D Au nanoparticle (NP) arrays show dispersive quality factors. These quality factors can be tailored simply by controlling NP height. Numerical calculations of near-field optical properties and band diagrams were performed to understand the measured dispersion effects of the OLPs. The results revealed that delocalized OLPs are a type of surface Bloch mode composed of many Bloch harmonics. As the OLP dispersion evolves from a stationary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 33 publications
5
56
0
Order By: Relevance
“…They suggested that delocalized OLPs are a kind of surface Bloch mode. As the OLP dispersion evolves from a stationary state to a propagating state, the nonradiative loss decreases because of weak local field confinement, whereas the radiative loss increases because of strong coupling to the leaky zero‐order harmonic . In the case of out‐of‐plane excitation, the lattice geometry contributes significantly since stronger coupling occurs in all directions within the plane of the array, as studied by the group of Boyd …”
Section: Spectroscopic Properties Of Tunable Plasmonic Latticesmentioning
confidence: 99%
“…They suggested that delocalized OLPs are a kind of surface Bloch mode. As the OLP dispersion evolves from a stationary state to a propagating state, the nonradiative loss decreases because of weak local field confinement, whereas the radiative loss increases because of strong coupling to the leaky zero‐order harmonic . In the case of out‐of‐plane excitation, the lattice geometry contributes significantly since stronger coupling occurs in all directions within the plane of the array, as studied by the group of Boyd …”
Section: Spectroscopic Properties Of Tunable Plasmonic Latticesmentioning
confidence: 99%
“…The SPR in metallic periodic structures can be excited when the Bragg condition is satisfied. 21 This type of diffractive coupling has been widely observed in arrays of nanoparticles [22][23][24][25] and nanoholes. [26][27][28] The SPR red shifts as the periodicity of the arrays increases as shown in both the experimental and the simulation results (Figure 2a and Figure 2b, respectively).…”
Section: Resultsmentioning
confidence: 90%
“…When the diffraction order changes from evanescent to radiative, a strong dipolar interaction takes place and collective modes could be observed, with the diffraction edge of the 0; 1 superstrate and substrate orders as λ air 0;1 d y and λ sub 0;1 n × d y , respectively. LPMs exhibit several novel characteristics compared with LSPRs, especially the significant suppression of the plasmon radiative damping resulting in narrow resonance lineshape, which could be utilized in bio-sensing [22][23][24], laser action [25][26][27], or SERS [28]. However, most of the LPMs reported were achieved by fabricating Au NPs on the substrate using electron beam lithography.…”
mentioning
confidence: 99%